2008
DOI: 10.1108/13619322200800010
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of Individuals with Korsakoff Syndrome: A Pilot Study of Supported Group Living in Northern Ireland

Abstract: As rates of dangerous drinking increase, services must improve their understanding of the needs of people with alcohol‐related brain damage such as Korsakoff syndrome (KS). This study looked at indications of change in key functioning areas for four people with KS living in a new supported living environment. The research highlighted the individualised and complex needs of people with KS and suggests that three specific factors may influence changes in functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Table 3 provides a summary of the psychosocial methods of assessing individuals with ARBD. Only two of the papers identified for inclusion in this review focused specifically on the use of psychosocial methods of assessing individuals with ARBD (Irvine & Mawhinney 2008, Oudman & Zwart 2012. Psychosocial methods of assessment were also used in three of the papers discussed above (Blansjaar et al 1992, Douglas & Wilkinson 1993, Oscar-Berman et al 2004.…”
Section: Neuropsychological Assessmentsmentioning
confidence: 99%
“…Table 3 provides a summary of the psychosocial methods of assessing individuals with ARBD. Only two of the papers identified for inclusion in this review focused specifically on the use of psychosocial methods of assessing individuals with ARBD (Irvine & Mawhinney 2008, Oudman & Zwart 2012. Psychosocial methods of assessment were also used in three of the papers discussed above (Blansjaar et al 1992, Douglas & Wilkinson 1993, Oscar-Berman et al 2004.…”
Section: Neuropsychological Assessmentsmentioning
confidence: 99%
“…Thus, it is also recommended that psychosocial interventions should focus on promoting family involvement, as well as encouraging the development of social support networks by facilitating engagement in meaningful social activities (Wilson et al, 2012). The reviewed evidence suggests that ARBD interventions should take place within supported accommodation facilities, as Blansjaar et al (1992) and Irvine and Mawhinney (2008) highlighted the potential value of specialist residential rehabilitation in enhancing social and behavioural functioning and improving physical and mental health. Morrison and Pestell, (2010) demonstrated the potential value of cognitive-behavioural interventions in promoting recovery from ARBD.…”
Section: Discussionmentioning
confidence: 99%
“…Lenanne (1986) and Monteiro et al (2011) demonstrated that the implementation of fixed daily routines, along with participation in alcohol-free recreational activities can increase levels of independence and spontaneity in individuals with ARBD. Moreover, Blansjaar et al (1992) and Irvine and Mawhinney (2008) provided evidence to suggest that specialist supported accommodation is beneficial in ARBD rehabilitation, as it facilitated independence as was associated with improvements in social, physical and behavioural functioning. A case study by Morrison and Pestell (2010) provided further evidence for the importance of psychosocial ARBD interventions, as an adapted cognitive-behavioural approach enabled the patient to challenge their unhelpful thoughts and assumptions and modify their behaviour, and resulted in improved mood.…”
Section: Psychosocial Interventionsmentioning
confidence: 98%
“…Too infrequently did only one or an inappropriate service, take responsibility for individuals, resulting in their care being segregated and sub-optimal (Thomson & Marshall 2006). In a UK qualitative study evaluating a newly constructed supported living environment, it was noted that people with ARBI were often placed in mental health facilities that did not have the resources to meet the complex needs of the people (Irvine & Mawhinney 2008). In Australia, specialist services for people with serious mental health issues are common, but people with ARBI, even when they have a concurrent mental illness encounter difficulties accessing treatment from them (Rota-Bartelink 2010).…”
Section: Inadequate Service Provision and Limited Care Pathwaysmentioning
confidence: 99%